Definição de folga entre matriz e punção a ser utilizado na operação de corte por cisalhamento - Saath, Criciliano Luiz (My University, 2025)
This study focused on the development and evaluation of an experimental tool designed for an in-depth investigation of the shear cutting process of metal sheets. The primary objective was to identify an ideal clearance between punch and die that would allow the cutting of different steel thicknesses (0.5 mm to 1 mm) without the need for die changes, thereby optimizing the production process. The research utilized a multifunctional die in a coil processing line with 304 stainless steel, conducting experiments by varying the radial clearance (5% to 25%).The results demonstrated that a constant radial clearance of 25% provided precise and high-quality cuts for both tested material thicknesses. The cut surface exhibited an adequate finish with minimal burrs. Microscopic analyses confirmed the absence of excessive material deformation and minimal tool wear even after multiple cycles, validating the efficiency of the multifunctional die design.The conclusion of this study is that determining an ideal cutting clearance, which enables the processing of various material thicknesses without the need for die changes, represents a significant advancement for the metalworking industry. This optimization will not only result in reduced setup times, increasing production volume and competitiveness, but also contribute to improved operator safety by minimizing exposure to risks during tool adjustments. In essence, this study demonstrates the potential of cutting clearance optimization as a fundamental pillar for efficiency, quality, and safety in the manufacturing of components by shearing. [resumo fornecido pelo autor]
Este trabalho focou no desenvolvimento e na avaliação de uma ferramenta experimental projetada para o estudo aprofundado do processo de corte de chapas metálicas por cisalhamento. O objetivo principal foi identificar uma folga ideal entre punção e matriz que permitisse o corte de diferentes espessuras de aço (0,5 mm a 1 mm) sem a necessidade de trocas de matriz, otimizando o processo produtivo. A pesquisa utilizou uma matriz multifuncional em uma linha de processamento de bobinas com aço inoxidável 304, realizando experimentos com variação da folga radial (5% a 25%).Os resultados demonstraram que uma folga radial constante de 25% proporcionou cortes precisos e de alta qualidade para ambas as espessuras de material testadas. A superfície cortada apresentou acabamento adequado, com poucas rebarbas. Análises microscópicas confirmaram a ausência de deformações excessivas no material e um desgaste mínimo da ferramenta mesmo após múltiplos ciclos, validando a eficiência do design da matriz multifuncional. A conclusão do estudo é que a determinação de uma folga de corte ideal, que possibilite o processamento de diversas espessuras de material sem a necessidade de trocas de matriz, representa um avanço significativo para a indústria metalomecânica. Essa otimização não apenas resultará na redução dos tempos de setup, aumentando o volume de produção e a competitividade, mas também contribuirá para a melhoria da segurança dos operadores, minimizando a exposição a riscos durante ajustes de ferramentas. Em síntese, este estudo demonstra o potencial da otimização da folga de corte como um pilar fundamental para a eficiência, qualidade e segurança na manufatura de componentes por cisalhamento. [resumo fornecido pelo autor]
Keywords: Cisalhamento; Produtividade industrial